2021
DOI: 10.1021/acs.jpca.1c07737
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Structural and Thermochemical Properties of [2.2.2]-Bicyclooctadiene Photoswitches

Abstract: Molecular photoswitches can under certain conditions be used to store solar energy in the so-called molecular solar thermal storage systems, which is an interesting technology for renewable energy solutions. The current investigations focus on the performance of seven different density functional theory (DFT) methods (B3LYP, CAM-B3LYP, PBE0, M06-2X, ωB97X-D, B2PLYP, and PBE0DH) when predicting geometries and thermochemical properties of the [2.2.2]-bicyclooctadiene (BOD) photoswitch. We find that all of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Furthermore, the systems have relatively long thermal back reaction times. However, we have recently reported that the storage energy can be significantly increased by altering the bridging unit of the NBD/QC system, a line of thought, which we will expand upon here. , …”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the systems have relatively long thermal back reaction times. However, we have recently reported that the storage energy can be significantly increased by altering the bridging unit of the NBD/QC system, a line of thought, which we will expand upon here. , …”
Section: Introductionmentioning
confidence: 91%
“…Calculations have been performed in Gaussian16 . This methodology is chosen as earlier studies have shown good performance for both NBD/QC and BOD/TCO systems. , Subsequently, we refine the electronic energy of the determined structures using the newly developed cluster perturbation theory CPS­(D-4) model in LSDalton, ,, which provides energies of CCSD quality at a low cost, while we utilize the vibrational and entropic energy contributions of the DFT calculations. The resulting storage energies are given in Table .…”
Section: Thermochemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The storage energy for the unsubstituted NBD/QC system is 0.97 MJ kg −1 while the corresponding value for the unsubstituted BOD/TCO is 1.77 MJ kg −1 . 24 Therefore, we became interested in evaluating BODs as candidates for MOST. Known BOD systems absorb in the UV range of the solar spectrum, 25 and molecular engineering is needed to red-shift the absorption spectrum towards more intense parts of the solar spectrum.…”
Section: Introductionmentioning
confidence: 99%